DEMOCRACY, FEDERALISM AND GOVERNANCE IN NIGERIA (Journal of Governance and Development (JGD), 2024)
Nigeria became one of the federal societies under the supervision of the British colonial government in 1954. Federalism and democracy ceased when the military government usurped and suspended the Republican Constitution in 1966. The periods of military rule witnessed over-centralization of power at the centre, while the federating states became Lilliputians. The usurpation of jurisdictional competencies and centralization of power made the federating states and local governments default on their socio-economic responsibilities. The paper aims to elucidate the intricate relationship between federalism and democracy in Nigeria, shedding light on the repercussions of their erosion during military rule. Through a comprehensive review of historical events and constitutional changes, this study examined the consequences of over-centralization and jurisdictional encroachments during military governance. The paper revealed that the institutionalization of federalism once embraced without due consideration, led to detrimental adjustments and crises during military rule, significantly impeding socio-economic and political development. The paper concluded that democracy and federalism are twins ‘brothers’ and will remain relevant and last long when Nigerian leaders, particularly elected representatives, undertake constitutional reforms that prioritized power devolution to states and local governments. This adjustment, rooted in justice and fairness, will rejuvenate the symbiotic relationship between democracy and federalism, ensuring lasting relevance.